Documentation of wild and underutilized vegetables:potential for conservation and utilization - Regmi, Milan; Shrestha, Aashish; Paudel, Hem Raj (Banko Janakari, 2022)
Wild and underutilized vegetables are important sources of food, nutrition, and income for rural communities and indigenous people. Cultivation of high-yielding hybrid varieties, change in food habits, climate change and over-harvesting have resulted in genetic erosion of these vegetables. In addition to this, their availability, distribution and uses are poorly documented. This study aims to document the wild, neglected, and underutilized vegetable species in Jaimini Municipality of Baglung District, Western Nepal. Complete information on wild and underutilized vegetables were collected using semi-structured interviews, guided field walks, and field observation. We recorded 64 species of wild and underutilized vegetables belonging to 27 different families in the study area. Leaf was the most used plant part (26 species) and majority of the plants species were herbs (33 species). Most of these vegetables were consumed in rainy and summer seasons and their availability decreased during winter season. Knowledge regarding their utilization, cultivation, and conservation were also gradually disappearing. Therefore, consumer awareness, evaluation of their nutritional value, and promotion for their commercial use should be emphasized for the inclusion of these vegetable species in our daily diet.